Simulations of ultra-high energy cosmic rays in the local Universe and the origin of cosmic magnetic fields. Issue 2 (4th January 2018) - Hackstein, S; Vazza, F; Brüggen, M; Sorce, J G; Gottlöber, S
Abstract: We simulate the propagation of cosmic rays at ultra-high energies, ≳10 18  eV, in models of extragalactic magnetic fields in constrained simulations of the local Universe. We use constrained initial conditions with the cosmological magnetohydrodynamics code enzo . The resulting models of the distribution of magnetic fields in the local Universe are used in the CRPropa code to simulate the propagation of ultra-high energy cosmic rays. We investigate the impact of six different magneto-genesis scenarios, both primordial and astrophysical, on the propagation of cosmic rays over cosmological distances. Moreover, we study the influence of different source distributions around the Milky Way. Our study shows that different scenarios of magneto-genesis do not have a large impact on the anisotropy measurements of ultra-high energy cosmic rays. However, at high energies above the Greisen–Zatsepin–Kuzmin (GZK)-limit, there is anisotropy caused by the distribution of nearby sources, independent of the magnetic field model. This provides a chance to identify cosmic ray sources with future full-sky measurements and high number statistics at the highest energies. Finally, we compare our results to the dipole signal measured by the Pierre Auger Observatory. All our source models and magnetic field models could reproduce the observed dipole amplitude with a pure iron injection composition. Our results indicate that the dipole is observed due to clustering of secondary nuclei in direction of nearby sources of heavy nuclei. A light injection composition is disfavoured, since the increase in dipole angular power from 4 to 8 EeV is too slow compared to observation by the Pierre Auger Observatory.